Non-Native Cooperative Interactions Modulate Protein Folding Rates - Bruno Da Silva, Fernando [UNESP]; Contessoto, Vinícius G.; De Oliveira, Vinícius M. [UNESP]; Clarke, Jane; Leite, Vitor B. P. [UNESP] (My University, 2018)
The energy landscape theory and the funnel description have had remarkable success in describing protein folding mechanisms and function. However, there are experimental results that are not understood using this approach. Among the puzzling examples are the α-spectrin results, in which the R15 domain folds 3 orders of magnitude more rapidly than the homologous R16 and R17, even though they are structurally very similar to each other. Such anomalous observations are usually attributed to the influence of internal friction on protein folding rates, but this is not a satisfactory explanation. In this study, this phenomenon is addressed by focusing on non-native interactions that could account for this effect. We carried out molecular dynamics simulations with structure-based C α models, in which the folding process of α-spectrin domains was investigated. The simulations take into account the hydrophobic and electrostatic contributions separately. The folding time results have shown qualitative agreement with the experimental data. We have also investigated mutations in R16 and R17, and the simulation folding time results correlate with the observed experimental ones. We suggest that the origin of the internal friction, at least in this case, might emerge from a cooperativity effect of these non-native interactions.